2023
DOI: 10.1002/biot.202200575
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of extracellular vesicles from human plasma samples: The importance of controls

Abstract: Background: Extracellular vesicles (EV) are enriched with proteins and RNA cargo, promoting cell-to-cell communication. Biofluid derived EV cargo is used for discovering disease specific markers for diagnosis and disease monitoring.Rational: Blood is a complex fluid with an abundance of protiens and thus isolation of EVs is challenging. Therefore, methods for EV isolation, including commercial kits use thromboplastin D (TP-D) for pretreatment of plasma to increase EV purity and yield. This pretreatment can int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Therefore, developing a standardized methodology to functionalize plasma-derived EVs could have broader implications for targeted drug delivery and personalized medicine. Furthermore, it has to be taken into account that plasma is one of the most difficult body fluids to isolate EVs from due to the presence of a massive pattern of particles . Plasma proteins and protein aggregates, as well as the large set of lipidic nanoparticles, represent the most abundant contaminants .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing a standardized methodology to functionalize plasma-derived EVs could have broader implications for targeted drug delivery and personalized medicine. Furthermore, it has to be taken into account that plasma is one of the most difficult body fluids to isolate EVs from due to the presence of a massive pattern of particles . Plasma proteins and protein aggregates, as well as the large set of lipidic nanoparticles, represent the most abundant contaminants .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has to be taken into account that plasma is one of the most difficult body fluids to isolate EVs from due to the presence of a massive pattern of particles. 39 Plasma proteins and protein aggregates, as well as the large set of lipidic nanoparticles, represent the most abundant contaminants. 40 The commonly used methods to separate plasma-EVs are based on the size or density.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our results indicated that among the different isolation methods, the EVs-UC isolates were especially prone to protein aggregation and to show albumin expression. To improve the purity of isolated EVs, an albumin-depletion step is usually introduced [ 37 , 38 ]. However, this is not possible when handling limited plasma volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is also considered the most physiological milieu to study blood EVs, taking into account that the number of EVs is higher in serum due to clot-induced platelet vesiculation [35]. Recently, comparisons of fresh versus frozen plasma found no significant difference in protein content of enriched EVs, which may further boost the use of biobanked plasma for EV research [37].…”
Section: Discussionmentioning
confidence: 99%
“…The protease thromboplastin-D converts prothrombin to thrombin during the clotting of blood, while the enzyme thrombin facilitates blood clotting by converting fibrinogen to fibrin. Relative to untreated plasma, pre-treatment with thromboplastin-D was reported to (i) remove clouding factors and prevent aggregation of ExoQuick enriched EVs [39], and (ii) not introduce contaminants, when using human recombinant thromboplastin and enriching for EVs using ultracentrifugation [37], though use of rabbit thromboplastin introduced exogenous tau contaminants [25]. Thrombin pre-treatment, unlike that observed with rabbit thromboplastin, lacked exogenous tau contaminants [25].…”
Section: Discussionmentioning
confidence: 99%